2016
DOI: 10.1016/j.humpath.2016.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic small vessel neoplasm, a rare infiltrative vascular neoplasm of uncertain malignant potential

Abstract: Summary Characteristic but rare vascular neoplasms in the adult liver composed of small vessels with an infiltrative border were collected from an international group of collaborators over a 5-year period (N = 17). These tumors were termed hepatic small vessel neoplasm (HSVN), and the histologic differential diagnosis was angiosarcoma (AS). The average age of patients was 54 years (range, 24–83 years). HSVN was more common in men. The average size was 2.1 cm (range, 0.2–5.5 cm). Diagnosis was aided by immunohi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 31 publications
2
50
0
Order By: Relevance
“…Mutations in the GNAQ family appear to be common among a variety of sporadic and congenital small vessel lesions. [5][6][7][8]10 Similar to our findings, mutually exclusive mutations in this family have been identified in congenital haemangiomas and capillary malformations. 5,8 Many of these distinct pathological entities have unique histological features and clinical presentations, so factors other than mutations in genes of the Gaq family probably account for these differences.…”
Section: Recurrent Gna14 Mutations In Anastomosing Haemangiomassupporting
confidence: 84%
“…Mutations in the GNAQ family appear to be common among a variety of sporadic and congenital small vessel lesions. [5][6][7][8]10 Similar to our findings, mutually exclusive mutations in this family have been identified in congenital haemangiomas and capillary malformations. 5,8 Many of these distinct pathological entities have unique histological features and clinical presentations, so factors other than mutations in genes of the Gaq family probably account for these differences.…”
Section: Recurrent Gna14 Mutations In Anastomosing Haemangiomassupporting
confidence: 84%
“…c-Myc, GLUT1, p53, and Ki-67 have been reported to be effective markers for distinguishing angiosarcoma from hepatic small vessel neoplasm, a more benign vascular neoplasm. 11 In this case, the angiosarcomatoid cells were positive for c-Myc on immunohistochemical staining. The expression of GLUT1 was not significantly higher in these cells than in other parts of the tumor.…”
Section: Discussionmentioning
confidence: 63%
“…Angiosarcomatoid cells diffusely expressed CD31 and factor VIII, and a small portion of angiosarcomatoid cells expressed CD34. c‐Myc, GLUT1, p53, and Ki‐67 have been reported to be effective markers for distinguishing angiosarcoma from hepatic small vessel neoplasm, a more benign vascular neoplasm . In this case, the angiosarcomatoid cells were positive for c‐Myc on immunohistochemical staining.…”
Section: Discussionmentioning
confidence: 69%
“…Usually, it appears as a homogeneous mass that strongly enhances in the early phases of the dynamic study, with varied enhancement patterns in the late phase. 79,80 We have recently collaborated to an international network study headed by Gill et al, 81 collecting 17 of these cases, unified under the category of "hepatic small vessel neoplasm (HSVN)," a tumor more common in adult men (mean age: 54 years), usually without comorbidities. Lewis et al 79 reported a similar case of small vessel hemangioma occurring in a patient with cirrhosis.…”
Section: Hepatic Small Vessel Neoplasmmentioning
confidence: 99%
“…Strong p53 and diffuse c-Myc staining were also significantly associated with angiosarcoma, but not with HSVN or cavernous hemangioma. 81 Capture based next generation sequencing using an assay that targets the coding regions of more than 500 cancer genes identified an activating hotspot GNAQ mutation in two of three (67%) tested samples, and one of these cases also had a hotspot mutation in PIK3CA. 81 Mutations previously reported in hepatic angiosarcoma were not found in this rather small sample of cases of HSVN.…”
Section: Hepatic Small Vessel Neoplasmmentioning
confidence: 99%